Cordyceps cateniannulata: its endophytic capacity and two-in-one biocontrol agent for coffee leaf rust and two coffee pests - Bautz, Keminy Ribett (2023)
Coffee is one of the most important agricultural products in the global economy. Coffee leaf rust, caused by Hemileia vastatrix, is the worst of all coffee diseases, and coffee berry borer – Hypothenemus hampei and coffee leaf miner Leucoptera coffeella – are the two main insect pests of coffee. The management of this disease and these pests is mainly carried out by the application of chemicals products and, however, their management continues to challenge farmers and researchers. Biological control by entomopathogenic fungi is a strategic tool in the fight against diseases and pests that threaten coffee production. Typically, members of the fungal genus Cordyceps are best known as obligate parasites of arthropods. However, there is increasing evidence that Cordyceps, and related genera in the Hypocreales, can grow both as plant endophytes and as parasites of arthropods. Cordyceps cateniannulata was isolated from healthy coffee tissues in Cameroon during a survey for fungi antagonistic to H. vastatrix. Preliminary tests have shown that C. cateniannulata is a mycoparasite of H. vastatrix. Since the genus Cordyceps (Cordycipitaceae: Hypocreales) is well known as including species that are pathogens it was hypothesized that C. cateniannulata could be pathogenic to two of the manly pests of coffee. In the present study, we present results pertaining to the potential of C. cateniannulata as a two-in-one biocontrol agent for the management of coffee leaf rust and two coffee pests, in addition to its endophytic colonization of coffee. In chapter 1, we evaluated the systemic endophytic capacity of C. cateniannulata in coffee seedlings, effects of C. cateniannulata against uredospores of H. vastatrix and the pathogenicity of C. cateniannulata against insect pests of coffee and also the beetle Tenebrio molitor as a model. By recovering C. cateniannulata from inoculated coffee plants, via both soil drench and foliar applications, we confirmed its endophytic status. Further controlled inoculation studies showed that this strain of C. cateniannulata is also a mycoparasite of coffee leaf rust, as well as an entomopathogen; infecting and killing coffee berry borer and coffee leaf miner. In chapter 2, we evaluated the virulence of C. cateniannulata against T. molitor and H. hampei under laboratory conditions, a comparison of the virulences of C. cateniannulata and Beauveria bassiana against H. hampei and a test of the application of C. cateniannulata to coffee branches against H. hampei under field cage-test conditions. Cordyceps cateniannulata caused a significant concentration- dependent increase in insect mortality. No difference was found between the virulence of C. cateniannulata and B. bassiana to H. hampei in this essay. Under this preliminary field cage test study, C. cateniannulata application resulted in a small but significant reduction in insect survival but it did not reduce the number of fruits bored by coffee berry borer. In chapter 3, we evaluated the potential of C. cateniannulata against coffee leaf miner in an in planta experiment and compared the potential of C. cateniannulata, B. bassiana and a mixture of both fungi in the same assay. In addition, we investigated the interaction between C. cateniannulata and B. bassiana in an in vitro assay. Cordyceps cateniannulata and B. bassiana, as well as the mixture, caused high mortality of coffee leaf miner pupae and no significant difference was found between the treatments. Furthermore, no synergistic effect was observed on pupal mortality after application of the mixture of both fungi; however, C. cateniannulata sporulated in more pupae than B. bassiana. In the in vitro experiment, C. cateniannulata alone and in coculture showed larger colony sizes than B. bassiana alone and in coculture. Moreover, there was no halo of inhibition for either fungus. Here, we provide a report on the potential of C. cateniannulata as novel entomopathogenic fungus to be deployed for the control of coffee leaf rust, coffee berry borer and coffee leaf miner. Keywords: Biological control. Entomopathogenic fungi. Fungal endophytes. Hemileia vastatrix. Hypothenemus hampei. Leucoptera coffeella. Mycoparasites.